Consumo e meio ambiente: estudo de caso sobre os consumidores que frequentam um restaurante de alimentação orgânica na cidade de Curitiba - Belnoski, Alexsandra Marilac (2007)
This paper presents an analysis of the sustainable development theories and its relation with today's society consumption patterns, as it has abruptly increased in recent years despite the industrialization process. Even though, there are some authors aggravated environmetnal issues, on the other hand, some others prefer to argue that this problem could possibly influence mankind to achieve greatness and higher wellbeing levels. This project is aimed at assessing to what extent a group of people perceive the presence of environmental awareness in our day-to-day lives. Hence this paper is proposed to analyse the relationship between our environment and food consumption patterns who advocate this should be a best- practice to achieve sustainable development in a contemporany society, In addition it is expected that this project will further influence the debate regarding consumption versus environment, through the case study from the theoretical reference of social repreentations with the aim of evaluating whether or not the concern with our environment is present in a selected group of people that frequently visit a restaurant that serves organic food in the city of Curitiba, in the State of Parana. Surprisingly once this dara has been processed and analysed, it was noted that this goup of peopel was primarily concerned wiyh their own wellbeing as oppsed to be contributing to the sustainable development of the environment. This perspective can be explained based on the benefits that toxic-free foods can bring to one's wellbeing. As such one can conclude that this group of people should be considered individualists because of the lack of collective awareness, since they centralize the benefits from organic food to their own wellbeing, instead of focusing the matter on the environment which is not a priority.